Quantification of the spatial distribution of rectally applied surrogates for microbicide and semen in colon with SPECT and magnetic resonance imaging - Cao, Ying J.; Caffo, Brian S.; Fuchs, Edward J.; Lee, Linda A.; Du, Yong; Li, Liye; Bakshi, Rahul P.; Macura, Katarzyna; Khan, Wasif A.; Wahl, Richard L.; Grohskopf, Lisa A.; Hendrix, Craig W. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Rectally applied drugs have been imaged using radioisotopes and magnetic resonance contrast agents. However, prior studies have not described the distribution and clearance of rectally‐applied drugs in quantitative terms with respect to complex three dimensional paths through the gastrointestinal tract. Such tools would allow statistical comparisons of candidate products in development or comparison of drug product with the distribution of a drug target, for example, HIV infected seminal fluid. WHAT THIS STUDY ADDS • New quantitative spatial parameters, derived from three dimensional curve fitting, have been successfully applied in this study to quantify the distribution of rectally‐applied gels. Indirect assessment using nuclear medicine techniques avoided the distortion and redistribution associated with sigmoidoscopic sampling. Thus, these measurements can be repeated over time to create concentration–distance–time surfaces to describe rectal product distribution and clearance within the gastrointestinal lumen to inform microbicide and other rectal product development. AIMS We sought to describe quantitatively the distribution of rectally administered gels and seminal fluid surrogates using novel concentration–distance parameters that could be repeated over time. These methods are needed to develop rationally rectal microbicides to target and prevent HIV infection. METHODS Eight subjects were dosed rectally with radiolabelled and gadolinium‐labelled gels to simulate microbicide gel and seminal fluid. Rectal doses were given with and without simulated receptive anal intercourse. Twenty‐four hour distribution was assessed with indirect single photon emission computed tomography (SPECT)/computed tomography (CT) and magnetic resonance imaging (MRI), and direct assessment via sigmoidoscopic brushes. Concentration–distance curves were generated using an algorithm for fitting SPECT data in three dimensions. Three novel concentration–distance parameters were defined to describe quantitatively the distribution of radiolabels: maximal distance (Dmax), distance at maximal concentration (DCmax) and mean residence distance (Dave). RESULTS The SPECT/CT distribution of microbicide and semen surrogates was similar. Between 1 h and 24 h post dose, the surrogates migrated retrograde in all three parameters (relative to coccygeal level; geometric mean [95% confidence interval]): maximal distance (Dmax), 10 cm (8.6–12) to 18 cm (13–26), distance at maximal concentration (DCmax), 3.8 cm (2.7–5.3) to 4.2 cm (2.8–6.3) and mean residence distance (Dave), 4.3 cm (3.5–5.1) to 7.6 cm (5.3–11). Sigmoidoscopy and MRI correlated only roughly with SPECT/CT. CONCLUSIONS Rectal microbicide surrogates migrated retrograde during the 24 h following dosing. Spatial kinetic parameters estimated using three dimensional curve fitting of distribution data should prove useful for evaluating rectal formulations of drugs for HIV prevention and other indications.